A Rare Pediatric Tumor: Supratentorial High-Grade Astroblastoma Presenting as a huge Mass - Sürmeli, Deniz; Urfalı, Boran; Özgür, Tümay (Indian Journal of Neurosurgery, 2023)
Background Astroblastoma is a rare neuroepithelial tumor of unknown origin, usually seen in children and young adults. It is usually localized to the cerebral hemisphere. Computed tomography and magnetic resonance imaging show a well-demarcated, contrast-enhancing mass with a cystic area. Characteristic histological findings are perivascular pseudorosette formation and frequent vascular hyalinization. The presented case is a 3.7-month-old female patient diagnosed with high-grade astroblastoma.Case Presentation We report the case of a 3.7-year-old female patient admitted to the neurosurgery clinic with strabismus for 25 days. Magnetic resonance imaging revealed a contrast-enhancing mass that contained cystic and necrotic areas. The tumor mass has been totally resected and histological examination combined with immunohistochemical study confirmed the diagnosis of high-grade astroblastoma.
Keywords: astroblastoma; brain; neuroepithelial